PEMANFAATAN E-COMMERCE DAN MEDIA SOSIAL UNTUK MENINGKATKAN PEMASARAN PRODUK USAHA AZZAHRA CRAFT DI DESA PUTY KECAMATAN BUA - Daming, Ahmad Syukur; Arnama, I Nyoman (Transpublika Publisher, 2022)
This community service activity is carried out by involving one partner, namely Azzahra Craft's home-based business. This service partner is located in Puty Village, Bua District, Luwu Regency and the business carried out is engaged in handicrafts, namely making hijab brooches on a small scale or at home. However, the media used in product marketing only uses the Whatsapp application and posts on Facebook so that product marketing is not optimal which causes its reach to only be within the scope of friends and family. The purpose of implementing this community service activity is the use of E-Commerce in Indonesia such as Shopee and Tokopedia as well as social media such as Instagram so as to increase the reach of product marketing to be wider. The method used in this activity is a participatory method, mentoring and training. The results obtained from the implementation of this community service activity are that training in the use of E-Commerce and social media can increase the motivation and knowledge of partners in marketing their products so that their turnover and income can increase.